Lost in SPACES: exploring the benefits and shortcomings of spatial presence and awareness as a mechanism for context reasoning - Coverdale, S (2016)
Context-Aware applications make use of sensed and gathered information about a user’s state to better tailor their behaviour to the user’s needs. There are many streams of information that can be employed as context; these elements have a variety of structures and not all of them are static or fully known to developers at runtime, this can make it challenging to add new streams of context to an application and keep those streams whose structure frequently changes updated. Heterogeneity of sensor technology and information sources means two users may generate information about the same aspect of their state, their location for example, in two different formats. Although there are examples of services that can relate a value from one location sensing technology to a value from another, we lack a general service for building and reasoning about these relationships between any and all representations of context. Moreover, due to their frequent use of sensed physical information, context-aware applications also generate seams, which may cause uncertainty, error and unexpected behaviours. Developers need a simple way to think about context; one which supports the many heterogeneous types of information it comprises, allows them to update the structures of those types as they change or are discovered, gives them the means to reason about relationships between users whose devices sense the same sort of context using different technologies, and which provides them with both opportunity and means to address and respond to some of the seams arising in their applications.